Unveiling the Link Between Sustainability Practices and Corporate Performance: A Case Study Approach - Arifin, Arifin (AGUSPATI Research Institute, 2025)
This study explores the intricate relationship between sustainability practices and corporate performance using a qualitative case study approach. Recognizing that sustainability has moved beyond a peripheral concern to a central business strategy, this research investigates how organizations perceive, adopt, and integrate sustainable practices into their operations. The study focuses on understanding the subjective experiences and managerial interpretations that link sustainability initiatives to financial and non-financial outcomes. By employing an in-depth case study method, the research captures the nuances of organizational decision-making and contextual factors influencing sustainability adoption. This approach allows for a holistic understanding of how sustainability contributes to value creation and long-term competitiveness.Data were collected through semi-structured interviews with managers, sustainability officers, and key stakeholders across selected companies recognized for their commitment to sustainability. Complementary evidence was gathered from internal documents, sustainability reports, and on-site observations to triangulate findings. Thematic analysis was employed to identify recurring patterns and critical themes that explain the interplay between sustainability practices and corporate performance. Emerging themes highlight the role of sustainability in enhancing corporate reputation, operational efficiency, and stakeholder trust. Furthermore, findings reveal the mediating influence of leadership commitment and organizational culture in embedding sustainability into strategic decision-making.The study contributes to the growing body of knowledge on sustainability accounting and management by offering qualitative insights that go beyond quantitative correlations. It underscores the importance of context-specific factors in shaping the outcomes of sustainability practices. The findings suggest that while sustainability practices enhance corporate performance, their impact is contingent upon managerial attitudes, resource allocation, and stakeholder engagement. The study also sheds light on challenges, including balancing short-term costs with long-term benefits and aligning sustainability initiatives with core business strategies. These insights provide practical implications for managers seeking to leverage sustainability as a driver of performance and resilience.This research offers both theoretical and practical contributions. Theoretically, it enriches the literature by demonstrating the mechanisms through which sustainability practices influence performance in real organizational settings. Practically, it provides evidence-based recommendations for companies aiming to integrate sustainability into their business models effectively. The case study findings highlight that sustainability is not merely a reporting exercise but a transformative process that shapes corporate identity and market positioning. Policymakers and regulators may also benefit from these insights in designing frameworks that encourage sustainable business practices. Ultimately, the study emphasizes that sustainability, when strategically managed, is a catalyst for long-term corporate success.